Control of STA1 gene expression by the mating-type locus in yeasts. - Yamashita, I (1985)
Extracellular production of glucoamylase from the yeast Saccharomyces diastaticus carrying an STA1 gene (a structural gene for the enzyme) is repressed by the mating-type constitution a/alpha. We obtained mutants that were relieved from the mating-type control of the STA1 gene expression. Tetrad analysis showed that the mutation was closely linked to MATa. The mutation was complemented by a MATa2 gene; hence, it was designated mata2. Northern blot analysis revealed that the MATa2-mediated repression occurs at the posttranscriptional level.